Effective properties of undoped and Indium3+-doped tin manganese telluride (Sn1 − xMnxTe) nanoparticles via using a chemical bath deposition route - Boon-on P. (2017)
© 2017 Elsevier B.V. Tin manganese telluride nanoparticles (Sn 1−x Mn x Te NPs) were first synthesized on a niobium pentoxide (Nb 2 O 5 ) film using a chemical bath deposition (CBD) route. An individual particle size before and after indium (In 3+ ) doping of ∼70–150 nm was investigated with stoichiometric formation of the SnMnTe phase. Furthermore, a cubic or rocksalt structure of the Sn 0.938 Mn 0.062 Te phase was also kept incorporated in the structure. The plotted energy band gaps for undoped and In 3+ -doped samples were 2.17 and 1.83 eV, respectively. The reduction of photoluminescence (PL) spectra after In 3+ doping, while the indium dopant acted as a trap state incorporated in Sn 1−x Mn x Te NPs, showed enhanced charge separation and reduced charge recombination, which resulted in a higher charge density trapped in the conduction band of Nb 2 O 5 and was also confirmed by the result of anodic peaks in the cyclic voltammetry. These results suggest new possibilities in optoelectronic and electrochemical devices.